A ludicidade em escolas de tempo integral para a educação infantil - Pereira, Caroline Rebeca de Lima (2024)
The experiences in the Pedagogy Course with Supervised Internships in Early Childhood Education, carried out in a Municipal Center for Regular Early Childhood Education of the municipal network, in a private Full-Time and Semi-Full-Time school in the city of Natal, and teaching practice motivated the development of this research. The general objective is to identify challenges and possibilities of full-time education for young children. The specific objectives are: to discuss the influence of playfulness on children's development and learning; to identify the main difficulties teachers face in full-time schools. The methodology used was documental research. Data collection was conducted through a bibliographic review of studies on playfulness and Full-Time Education in the UFRN Institutional Repository. The theoretical foundation used in official documents and the research of Piaget (1983), Vygotsky (1991), and Kishimoto (2010) allow for the identification of the following results: the Full-Time School Program is a Federal Government strategy with financial support and technical assistance aimed at serving students in vulnerable situations, but it still requires improvements. Teachers face challenges related to infrastructure, continuous training, school-family relationships, and the objectives of the pedagogical proposal. Overcoming these challenges is emphasized to promote autonomy and learning for children. The research highlights significant contributions related to playfulness for improving the quality of teaching and learning in Full-Time Early Childhood Education, suggesting further studies.